1956
DOI: 10.1017/s0007485300046824
|View full text |Cite
|
Sign up to set email alerts
|

The Mosquitos of Liberia (Diptera: Culicidae), a general Survey

Abstract: In this, the third in a series of papers on the mosquito fauna of the African Eepublic of Liberia, the results of past studies and of a recent survey by the writer have been incorporated to present an up-to-date summary of all the available information on this little-known section of the Upper Guinean Forest. Bequaert (1930) quotes Ziemann (1902) as the first to report the presence of Anopheles gambiae Giles in Monrovia. Bequaert himself lists 18 species of mosquitos collected in Liberia during the Harvard Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1960
1960
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…51 As for Cx. rima, its presence has already been reported in some African countries, [52][53][54] but its vector role remains unknown to this day. We found that the fragment of the COI gene amplified in this study could not distinguish An.…”
Section: Mosquitoes Collection and Morphological Identificationmentioning
confidence: 99%
“…51 As for Cx. rima, its presence has already been reported in some African countries, [52][53][54] but its vector role remains unknown to this day. We found that the fragment of the COI gene amplified in this study could not distinguish An.…”
Section: Mosquitoes Collection and Morphological Identificationmentioning
confidence: 99%
“…vittatus are found predominantly in pools in rock outcrops or river beds, and even in pools formed in coral (Wiseman, Symes, MacMahon & Teesdale, 1939). They have also been recorded from a variety of habitats including domestic utensils, hoofprints, boats, wells (Hopkins, 1952), bamboo pots (Harris, 1942) and tree-holes (Kerr, 1933;Peters, 1956), and the present author has found larvae on several occasions at the peak of the breeding season in open floodwater concrete drains. In the present work, however, no larvae of Ae.…”
Section: Observations On Immature Stagesmentioning
confidence: 52%
“…These specimen records are the basis of the distribution maps , which were generated with SimpleMappr (https://www.simplemappr.net). Specimen records without coordinates were georeferenced using Google Earth, GEOnet Names Server (https://geonames.nga.mil/gns/html/), and the following literature sources: Arnold (1954), Balogh et al (1965), Baum (1903), Benson et al (1933), Bottego (1895), Bouvier (1922), Chamberlin (1927), Chapin (1954), davis & Misonne (1964), delachaux & Thiébaud (1934, donisthorpe (1945), dugmore (1910), Eltringham (1918), Evans & Fletcher (1952), Friedmann & Williams (1969), hocking (1970, Kizungu (2006Kizungu ( ), lamotte et al (2003Kizungu ( ), loveridge (1957, Martin et al (1909), Mason & rozkosny (2015), Molyneux (1903), O'leary (2003), Penzig (1895), Peters (1956), renaut & Owen (2005, room (1971), Tessmann (1913), Wheeler (1922b), Wittmer (1970), and Young (1917). Geolocation of some Ed ross collection sites was made possible by consulting his field notes and annotated maps in the archives of the California Academy of Sciences.…”
Section: Mfcmentioning
confidence: 99%